Challenges in coordinating response and rehabilitation activities during the Guimaras oil spill implications to the Philippine disaster management system - Ebay, Jorge S.; Lizada, Joy C. (2009)
This paper describes the response and rehabilitation activities during the August 11, 2006 oil spill in Guimaras. It outlines the implications of oil spill to the existing disaster management system, which provided for the strengthening of the Philippine disaster control capability and the establishment of the national program on community preparedness.

This paper argues that the current disaster management system in the country is constrained by operational factors that affect the overall management of both natural and human induced disasters. It presents evidences of actual response and rehabilitation activities carried out during the oil spill derived from agency reports and supplemented by findings during focus group discussions and key informant insights that can be useful in improving the overall system for disaster management in the country.
Keywords: Disaster Risk Reduction and Management (DRRM)